Dispensasi Kawin dengan Alasan Sangat Mendesak di Mojokerto: Analisis Yuridis atas Perma No. 5 Tahun 2019 - Hidayat, Arif; Evendi, Wakid; Darajaatul Aliyah, Nelud (State of Islamic Institute Langsa, 2024)
Ideally, the dispensation of marriage for urgent reasons is expected to provide a solution for couples caught in difficult situations, especially in the context of legal norms that protect individual rights. However, the implementation of marriage dispensation often faces challenges, particularly regarding the criteria and limitations set forth in Supreme Court Regulation No. 5 of 2019, leading to injustice for prospective brides and grooms. The aim of this research is to analyze the implementation of marriage dispensation at the Mojokerto Religious Court and assess the extent to which this regulation meets public expectations. This article is categorized as qualitative literature research, employing normative legal studies and comparative studies between classical scholars' thoughts and modern regulations. This research concludes two things: First, from a legal perspective, although challenges remain in its implementation in the field, Supreme Court Regulation No. 5 of 2019 provides clear guidelines for the dispensation of marriage. Second, the comparison between classical thought and modern regulations indicates a shift in focus from socio-cultural aspects to a more comprehensive protection of individual rights, reflecting the need for legal adaptation in response to evolving social dynamics.